2016
DOI: 10.3389/fneur.2016.00147
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Co-Occurring Gray Matter Concentration Loss across the Huntington Disease Prodrome

Abstract: Huntington disease (HD) is caused by an abnormally expanded cytosine–adenine–guanine (CAG) trinucleotide repeat in the HTT gene. Age and CAG-expansion number are related to age at diagnosis and can be used to index disease progression. However, observed onset-age variability suggests that other factors also modulate progression. Indexing prodromal (pre-diagnosis) progression may highlight therapeutic targets by isolating the earliest-affected factors. We present the largest prodromal HD application of the univ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 53 publications
3
18
1
Order By: Relevance
“…The SBM approach allowed us to identify spatial patterns of GM volume common to the cohort of MS patients in this study. Although SBM has been suggested to be more sensitive in detecting GM atrophy than other methods such as VBM ( Ciarochi et al, 2016 , Kasparek et al, 2010 ), we did not detect differences at baseline between patients split on CDP status at the end of the study. Nonetheless, the CDP patient group experienced a significantly greater rate of GM atrophy in two of the identified patterns.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…The SBM approach allowed us to identify spatial patterns of GM volume common to the cohort of MS patients in this study. Although SBM has been suggested to be more sensitive in detecting GM atrophy than other methods such as VBM ( Ciarochi et al, 2016 , Kasparek et al, 2010 ), we did not detect differences at baseline between patients split on CDP status at the end of the study. Nonetheless, the CDP patient group experienced a significantly greater rate of GM atrophy in two of the identified patterns.…”
Section: Discussioncontrasting
confidence: 89%
“…Although VBM is a conceptually simple approach to analyzing group data, our results suggest that it may lack a certain degree of sensitivity to GM atrophy, especially in a longitudinal setting. Similar discrepancies between SBM and VBM have been reported in cross-sectional studies of other neurological diseases such as schizophrenia ( Kasparek et al, 2010 ) and Huntington's disease ( Ciarochi et al, 2016 ). In the current study, Pattern 1, which underwent significantly greater atrophy in the CDP group, contained, in part, the anterior and posterior cingulate gyri, which were not identified by the VBM analysis.…”
Section: Discussionsupporting
confidence: 77%
“…We are not aware of any previous studies that analyzed pulsed ASL data in a setting similar to ours. So far, ICA studies that used source-based morphometry mainly analyzed structural MRI data in patients with schizophrenia (35,36) and, to a lesser degree, healthy participants (37,38) and patients with Huntington disease (39). Therefore, by applying ICA to three imaging modalities and especially by applying source-based morphometry to patients with AD and MCI for all three modalities, we offer an application of this method.…”
Section: Discussionmentioning
confidence: 99%
“…The CAP‐Age product (CAP) score is defined as CAP = Age*(CAG − 33.66) (Zhang, et al, ), where age is measured at the time of the scan. CAP scores have been used to estimate time to HD onset and to index HD progression accounting for exposure time to the toxic protein effects of CAG expansion (Ciarochi et al, ; Lee et al, ; Liu et al, ; Paulsen, Long, Ross, et al, ; Ross et al, ; Tabrizi et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Structural studies have demonstrated that prediagnosis and postdiagnosis HD progression is characterized by striatal atrophy and cortical changes (Aylward et al, ; Ciarochi et al, ; Myers et al, ; Paulsen et al, ; Vonsattel et al, ). Complementing these results, functional connectivity studies have generally shown reduced activation in the basal ganglia and cortical regions, suggesting that functional alterations also happen before HD motor symptoms (Koenig et al, ; Paulsen et al, ; Thiruvady et al, ).…”
Section: Introductionmentioning
confidence: 99%